Clinical and Molecular Epidemiological Study on Herpesviruses Infection among Equid Populations in Upper Egypt - Abdel-Rady, A; Abd El-Rahim, I; S. Gad El-Rab Abd El-Hameed; Malek, S (Journal of the Hellenic Veterinary Medical Society, 2023)
The present study was carried out to record the clinical signs of equine herpesviruses (EHVs) infection and to detect the prevalence of EHVs infection among working equids in different provinces of Egypt. A total number of 115 working equids (92 horses and 23 donkeys) were clinically examined and sampled from November 2018 till November 2019 for this study. Two samples were collected from each animal (nasal swab and blood sample) and were subjected to multiplex-PCR to detect the prevalence of different EHVs infection among equids. In the current study, the overall prevalence of EHVs infection among equid populations in Egypt was 80% by using multiplex-PCR. Moreover, the most prevalent equine herpesvirus (EHV) among equids in Upper Egypt was EHV-2 (61.74%), followed by EHV-5 (43.48%), EHV-1 (20%), and EHV-4 (13.04%). The recorded clinical signs of the examined equids harbored EHVs (PCR-positive) can be summarized as follow: a higher percentage was detected among equids with a history of acute onset (59.78%), pyrexia (57.61%), and/or systemic illness (45.65%) with or without respiratory signs (56.52%) and ocular signs (35.87%). Furthermore, 4.35% and 1.09% of EHV-1 PCR-positive equids displayed neurological signs and abortion, respectively.